On Some Properties of Generalized Fock Space $F^2(dv_α)$ by Frame Theory on the $C^n$ - Tatari, M.; Vaezpour, S. M.; Pishinian, A. (Communications in Mathematics and Applications, 2010)
We obtain a short and new sharp proof for atomic decomposition for Fock space on the $C^n$ by using the frame theory. In fact we show that the generalized Fock space $F^2(dv_α)$ on the $C^n$ admit an atomic decomposition i.e every analytic function in this space can be presented as a linear combination of "atoms" defined using the normalized reproducing kernel of this space.